2022
DOI: 10.1111/gcb.16119
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution fuels transcriptional plasticity to ocean acidification

Abstract: Ocean acidification (OA) is postulated to affect the physiology, behavior, and life‐history of marine species, but potential for acclimation or adaptation to elevated pCO2 in wild populations remains largely untested. We measured brain transcriptomes of six coral reef fish species at a natural volcanic CO2 seep and an adjacent control reef in Papua New Guinea. We show that elevated pCO2 induced common molecular responses related to circadian rhythm and immune system but different magnitudes of molecular respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 127 publications
8
53
0
Order By: Relevance
“…One of them is synaptic transmission and the down regulation of a lincRNA and the neighbouring coding CACNA1E (gene voltage-gated calcium channel complex) can contribute to synaptic transmission (Berecki et al, 2014), which was also found to behave similarly to a previous RNAseq A. polyacanthus data (Schunter et al, 2018). In addition, immune responses are commonly associated with ocean acidification in fish including our study species (De Souza et al, 2014;Kang et al, 2022;Machado et al, 2020), and here we find differential expression of lincRNAs neighbouring a variety of immune response genes that show co-expression in a gene network significantly correlated with CO2 levels. This reveals that lincRNAs annotated in our coral reef fish show differential expression in response to an environmental factor, CO2 levels, and that some of these differentially expressed lincRNAs are in close proximity to coding genes that are known to have functional implications in the response to ocean acidification in fishes.…”
Section: Functional Responses Of Lncrnas To Environmental Changesupporting
confidence: 73%
See 3 more Smart Citations
“…One of them is synaptic transmission and the down regulation of a lincRNA and the neighbouring coding CACNA1E (gene voltage-gated calcium channel complex) can contribute to synaptic transmission (Berecki et al, 2014), which was also found to behave similarly to a previous RNAseq A. polyacanthus data (Schunter et al, 2018). In addition, immune responses are commonly associated with ocean acidification in fish including our study species (De Souza et al, 2014;Kang et al, 2022;Machado et al, 2020), and here we find differential expression of lincRNAs neighbouring a variety of immune response genes that show co-expression in a gene network significantly correlated with CO2 levels. This reveals that lincRNAs annotated in our coral reef fish show differential expression in response to an environmental factor, CO2 levels, and that some of these differentially expressed lincRNAs are in close proximity to coding genes that are known to have functional implications in the response to ocean acidification in fishes.…”
Section: Functional Responses Of Lncrnas To Environmental Changesupporting
confidence: 73%
“…Furthermore, lncRNAs have been shown to regulate core circadian rhythm genes in mammals (Mosig & Kojima, 2021). With a substantial fraction of lncRNAs affecting the gene expression of their neighbouring coding genes (Engreitz et al, 2016), it is no surprise to see elevated expression in lncRNAs neighbouring GABA A receptor and core circadian rhythm genes as these are known to play important roles in the transcriptional response to ocean acidification (Kang et al, 2022; Schunter et al, 2021, 2016). As our RNAseq data is from ocean acidification experiments, this now hints at a regulatory involvement of lncRNAs in these key functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many coastal ecosystems experience significant environmental variability over a range of temporal scales, including fluctuations in seawater pH/ p CO 2 (Chan et al, 2017; Hofmann et al, 2011; Kang et al, 2022; Kroeker et al, 2020). In upwelling regions, where deeper, more acidic water is brought to the ocean surface, pH can vary by half a unit over a period of weeks (Hirsh et al, 2020; Hofmann et al, 2011).…”
Section: Introductionmentioning
confidence: 99%